The Impact of Digital Communication on Language Evolution among Urban Youth in Singapore - Lee, Stephanie (International Journal of Linguistics, 2024)
Purpose: The aim of the study was to analyze the impact of digital communication on language evolution among urban youth in Singapore. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on the found that digital platforms significantly influence language evolution among this demographic. It revealed a noticeable shift towards abbreviated forms, emoticons, and slang in everyday communication, driven by social media and instant messaging. Unique Contribution to Theory, Practice and Policy: Social network theory, diffusion of innovations theory & identity theory may be used to anchor future studies on the impact of digital communication on language evolution among urban youth in Singapore. Implement educational programs that enhance digital literacy skills among youth, focusing on critical evaluation of online content and responsible language use. Develop policies that promote digital inclusion and accessibility, ensuring all youth have equal opportunities to engage in online communication.